A novel type II crustin in the innate immune response of the freshwater crab (Sinopotamon henanense) against infection and its expression changes by cadmium. Issue 134 (March 2023) - Bao, Minnan; Liang, Yue; Lang, Lang; Chen, Chien Min; Zhang, Zuobing; Wang, Lan
Abstract: Antibacterial peptide (AMP), an effector of the innate immune system, is an essential component of invertebrate innate immunity. Crustin is a family of antimicrobial peptides that are widely studied in crustaceans. Here we report a novel crustin (designated Shcrustin ) from the freshwater crab Sinopotamon henanense . The results revealed that the full-length cDNA of Shcrustin was 691 bp with an open reading frame (ORF) of 510 bp. Phylogenetic analysis of the Shcrustin sequence showed that it clustered with type II crustin. Shcrustin exists in different tissues, among which the highest expression level is found in the gills. After the bacterial challenge, the expression of Shcrustin increased in hemocytes or gills. However, crustin expression was suppressed in the presence of cadmium (Cd). To elucidate the biological activity of Shcrustin, we constructed a recombinant Shcrustin protein. Purified rShcrustin could bind to a variety of bacteria and inhibit the growth of different bacteria indicating that Shcrustin has inhibitory activity against gram-positive and gram-negative bacteria. In addition, the phagocytic rate of hemocytes toward bacteria decreased after the interference of Shcrustin expression by RNA interference, suggesting that Shcrustin may be involved in such a process. Therefore, we conclude that Shcrustin may be involved in the innate immunity of S. henanense by binding to bacteria and promoting hemolymph phagocytosis to clear invading pathogens. It is an important immune effector against pathogen infection. In the presence of Cd, it may alter the expression of Shcrustin and suppress its immune function. Highlights: Antimicrobial peptides are important immune effector molecules in invertebrate innate immunity. Shcrustin is highly expressed in the gills, which can respond to the infection of A. hydrophila and S. aureus. Shcrustin may eliminate invading pathogens by binding to bacteria and promoting phagocytosis. Cadmium stress affects the expression pattern of Shcrustin.